Predictive value of EuroSCORE on long term outcome in cardiac surgery patients: a single institution study. (13th May 2005) - De Maria, R; Mazzoni, M; Parolini, M; Gregori, D; Bortone, F; Arena, V; Parodi, O
Abstract : Objectives: To assess the value of the European system for cardiac operative risk evaluation (EuroSCORE), a validated model for prediction of in-hospital mortality after cardiac surgery, in predicting long term event-free survival. Design and setting: Single institution observational cohort study. Patients: Adult patients (n = 1230) who underwent cardiac surgery between January 2000 and August 2002. Results: Mean age was 65 (11) years and 32% were women. Type of surgery was isolated coronary artery bypass grafting in 62%, valve surgery in 23%, surgery on the thoracic aorta in 4%, and combined or other procedures in 11%. Mean EuroSCORE was 4.53 (3.16) (range 0–21); 366 were in the low (0–2), 442 in the medium (3–5), 288 in the high (6–8), and 134 in the very high risk group (⩾ 9). Information on deaths or events leading to hospital admission after the index discharge was obtained from the Regional Health Database. Out of hospital deaths were identified through the National Death Index. In-hospital 30 day mortality was 2.8% (n = 34). During 2024 person-years of follow up, 44 of 1196 patients discharged alive (3.7%) died. By Cox multivariate analysis, EuroSCORE was the single best independent predictor of long term all cause mortality (hazard ratio (HR) 1.55, 95% confidence interval (CI) 1.03 to 2.34, p < 0.0001). In the time to first event analysis, 227 either died without previous events (n = 20, 9%) or were admitted to hospital for an event (n = 207, 91%). EuroSCORE (HR 1.60, 95% CI 1.36 to 1.89, p < 0.0001), the presence of ⩾ 2 co-morbidities versus one (HR 1.49, 95% CI 1.09 to 2.02, p < 0.0001), and > 96 hours' stay in the intensive care unit after surgery (HR 2.04, 95% CI 1.42 to 2.95, p = 0.0001) were independently associated with the combined end point of death or hospital admission after the index discharge. Conclusions: EuroSCORE and a prolonged intensive care stay after surgery are associated with long term event-free survival and can be used to tailor long term postoperative follow up and plan resource allocation for the cardiac surgical patient.